Recent labor force trends in Algeria - SABEUR CHOUIREF, MOKHTARIA; HAMANE , SORAYA (Journal of Human Sciences, 2023)
After independence in Algeria, the activity rate experienced significant growth. This rate has doubled in 53 years (between 1966 and 2019), it went from 21.20% in 1966 to 42.20% in 2019. This improvement in the situation is due to the economic growth experienced by Algeria and political and economic stability and by other several socio-economic factors such as the improvement of the health situation, the remarkable decline in general mortality and especially infant mortality. In this article, we will see the recent trend of the working population in Algeria.